RESOURCE PRODUCTIVITY AND ECO-EFFICIENCY – CONTEMPORARY CONCEPTS OF BUSINESS SUCCESS - Tomić, Slavica; Delić, Dragana B.; Stoiljković, Aleksandra (Poslovna ekonomija, 2018)
In the context of evident negative environmental  outcomes of economic activities, nowadays companies are under the pressure to accept clean (healthy) environment as a  „specific stakeholder” and to internalize harmful effects of business activities on natural resources. Since costs of environmental protection and pollution control are element of total costs, companies are striving to simultaneously improve economic and environmental performances and to achieve economically sustainable sustainability. Also, it is necessary to revise traditional concepts of business success and (re)define contemporary indicators. Recently, business success is evaluated through non labour resource productivity and eco-efficiency.
Keywords: resource productivity; eco-efficiency; business success; RESOURCES